Fluorescence turn-on detection of glucose via the Ag nanoparticle mediated release of a perylene probe. Issue 29 (12th March 2015) - Li, Juanmin; Li, Yongxin; Shahzad, Sohail Anjum; Chen, Jian; Chen, Yang; Wang, Yan; Yang, Meiding; Yu, Cong
Abstract : A novel fluorescence turn-on strategy based on the perylene probe and the silver nanoparticles for glucose sensing has been developed. Abstract : A novel fluorescence turn-on strategy for glucose sensing is demonstrated. The fluorescence of a perylene probe could be quenched by the silver nanoparticles (Ag NPs). The Ag NPs could be etched by H2 O2 generated from the enzymatic oxidation of glucose. And efficient probe fluorescence recovery was detected.